2014
DOI: 10.1002/14651858.cd005136.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion for stimulus deprivation amblyopia

Abstract: Background-Stimulus deprivation amblyopia (SDA) develops due to an obstruction to the passage of light secondary to a condition such as cataract. The obstruction prevents formation of a clear image on the retina. SDA can be resistant to treatment, leading to poor visual prognosis. SDA probably constitutes less than 3% of all amblyopia cases, although precise estimates of prevalence are unknown. In developed countries, most patients present under the age of one year; in less developed parts of the world patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…The impact of adherence to occlusion therapy on visual outcome is, therefore, difficult to assess. Further, although the efficacy of occlusion therapy for treating other types of amblyopia has been evaluated (9), its efficacy in children with unilateral congenital cataract has not been rigorously examined (10). …”
Section: Introductionmentioning
confidence: 99%
“…The impact of adherence to occlusion therapy on visual outcome is, therefore, difficult to assess. Further, although the efficacy of occlusion therapy for treating other types of amblyopia has been evaluated (9), its efficacy in children with unilateral congenital cataract has not been rigorously examined (10). …”
Section: Introductionmentioning
confidence: 99%
“…Such data are of importance in both research and clinical practice. In particular, a recent Cochrane Review recently recommended clinical trials be conducted to evaluate the efficacy of occlusion therapy for children with stimulus deprivation amblyopia, such as caused by unilateral cataract [3]. The methods we investigate here would allow for a quantitative estimation of adherence to occlusion therapy in such a trial.…”
Section: Discussionmentioning
confidence: 99%
“…Although occlusion is a standard part of treatment, its efficacy has not been rigorously assessed [3]. Further, because occlusion is often difficult for caregivers to administer [4, 5], there is a high-level of non-concordance between prescribed and achieved occlusion [611].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, while the present systematic review was inclusive of all types of amblyopia, only a small number of participants had form deprivation amblyopia. This was unavoidable due to the low levels of research carried out on this condition 30. Despite these limitations a core set of studies with moderate quality were identified and provide evidence that information giving is an effective method of improving compliance.…”
Section: Discussionmentioning
confidence: 99%